دوراﻟﺮوﺿﺔ ﻓﻲ ﺗﻨﻤﯿﺔ اﻟﻘﯿﻢ اﻟﺨﻠﻘﯿﺔ ﻟﺪى اﻷطﻔﺎل (Journal of the College of Education for Women, 2019)
The role of kindergarten in the development of moral values of children" The child moral education in institutions of basic education considered as the priority of values and social goals of methodical education , and consideringto how the child be in the kindergarten of susceptibility to absorb and configuration and modification of experiences, thus the kindergartens are important because of their influence in the formation of his character through reincarnation of the personality of those who manage education and try to imitate their values and attitudes and standards of right and wrong. This is also happen through his exercise of educational activities until he has moral insight which enables him to distinguish between good and evil behavior. The current research aims to whether the kindergarten's role in the development of moral values in children from the viewpoint of teachers and parents of children, and see if the moral values which the curriculum of kindergarten included is enough to achieve the right moral behavior for children from the viewpoint of the teacher, and whether that moral values learned by the child from the kindergarten curriculum is enough to achieve right moral behavior from the viewpoint of parents, and see if there were statistically significant differences in moral values learned by children in kindergarten depending on variable age (kindergarten, and preliminary), and to identify paragraphs that received the highest weight percentage and free degree of the items of moral values of the questionnaire of children teachers and their parents. The current research questionnaire, as a tool to collect the required information which has been prepared by the researcher, the research sample has reached (80) children, (44) females and (36) of males from kindergarten in Karkh and Rusafa in the city of Baghdad and in the age of kindergarten and preliminary, (80) teachers, and (80) from parents, distributed to kindergartens in the research sample of children. Researcher used Pearson correlation, equation and average hypothesis and the standard deviation and the arithmetic mean and weight percentile and the weighted average and T- testing for one sample and two independent samples for the purpose of verification of the objectives of the research. The researchfound the following results : -The kindergarten has a role in the development of moral values from the point of view of teachers and parents. - The ethical values contained in kindergarten curriculum are approximately enough to achieve right moral behavior for children from the point of view of the teacher. -The moral values that children learn through kindergarten curriculum are approximately enough to achieve moral behavior for children from the point of view of the parents of the children. - There are statistically significant difference to learn moral values from the point of view of teachers to the preliminary stage. The researcher also put some of the recommendations and proposals.